Ploughing the path to prosperity: India’s agricultural growth and its importance and challenges. (International Journal of Food and Nutritional Sciences, 2022)
India's agricultural sector has historically played a pivotal role in the country's economic development. This abstract explores the multifaceted contribution of agriculture to India's economic growth.Agriculture in India has been a major source of livelihood for a significant portion of its population, directly employing over half of the workforce. The sector's substantial labor absorption has contributed to poverty alleviation and rural development by providing income opportunities and improving living standards in rural areas.Furthermore, agriculture has been a vital contributor to India's GDP, providing essential raw materials for various industries, including textiles, agro-processing, and pharmaceuticals. It has also been a source of foreign exchange earnings through exports of agricultural products such as rice, wheat, spices, and tea.Food security, a fundamental aspect of agriculture, is integral to India's economic stability. Ensuring a consistent and adequate supply of food is crucial for a growing population. The Green Revolution in the 1960s and 1970s significantly increased agricultural productivity, ensuring a consistent food supply and stabilizing food prices.In conclusion, agriculture's multifaceted contribution to India's economic development is indisputable. Its role in providing employment, contributing to GDP, and supporting various industries underscores its significance. Moreover, the nexus between agriculture and food security is vital for ensuring the well-being of the nation's citizens and maintaining economic stability.